MINING INDUSTRY IN BUKHARA EMIRATE: FROM ECONOMIC DEPENDENCE TO POLITICAL DEPENDENCE - Abduraimova M. B. (TARIXIY TADQIQOTLAR, 2025)
This article provides information on mining operations in the Bukhara Emirate, the involvement of Russian mining experts, and country-wide research and development. Also, the results of Russian experts on the progress of mining works in the emirate were cited. At the same time, it was described that the complications and consequences of gold prospecting in this area caused political dependence.